MOTIVASI REMAJA PEREMPUAN MENGUNJUNGI COFFEE SHOP - Abrar, Muhammad Bintang; Widodo, Teguh (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Motivation is a psychological symptom that appears in a person consciously or unconsciously to take action with a specific purpose. For this reason, it can be concluded that motivation is a process that occurs both consciously and unconsciously to carry out certain actions that aim to meet needs so that an individual feels satisfied with that goal. With the motivation that encourages young girls to visit the Coffee Shop, from there a shift in meaning appears, from where the Coffee Shop was originally just a Coffee Shop, now they interpret it as a place of entertainment because the Coffee Shop now has many facilities. Hanging out culture is one of the many types of culture that exist. We can see this cultural pluralism in terms of attitudes, ways of life, and values that exist within certain groups. Hanging out at the Coffee Shop has become a lifestyle for modern society in Pekanbaru City, one of the Coffee Shops is the Kala Bumi Coffee Shop. This study aims to find out what motivates young girls to visit the Coffee Shop and how young women interpret Coffee Shops as a place of entertainment. The selection of subjects in this study used a purposive sampling method with characteristics of teenage girls who had an age range of 17-24 years and had visited the Kala Bumi Coffee Shop at least three times in the past month. Keywords: Motivation, Coffee Shop, Lifestyle